Aktualisasi Dakwah di Era Teknologi Komunikasi - Arifah Yenni Gustia (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Dakwah is an effort to call for all human race about the life’s vision and mission in the world consisting of amar ma’ruf nahi munkar (a call for good deeds and avoiding bad ones) using either spoken or written with any medias allowed. Basically, there are so many and so wide methods and tools for dakwah. And the technology today has grown so fast. Various telecommunication technologies compete in giving unlimited information. The world has been transforming globally in term of information and communication resulting a new civilization to ease humans to interact each other and to enhance social mobility. The presence of communication technology has become the means of dakwah for da’i (Islamic preachers) in this modern era and has given huge influence towards the people themselves. A message of them can be obtained by people in a very short time